2011
DOI: 10.1021/jo102597d
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity in Nucleophilic Additions to 3-Azidoalkanals

Abstract: The stereoselectivity of nucleophilic additions to 3-azidoalkanals was investigated. Non-chelating, BF(3)·OEt(2)-mediated Sakurai addition to 3-azidoalkanals afforded 1,3-anti products, whereas use of a chelating Lewis acid, TiCl(4), resulted in 1,3-syn products with moderate selectivity. A boat-like chelation structure of the 3-azidoalkanal with the Lewis acid is proposed to be consistent with the 1,3-syn selectivity of the reactions. Mukaiyama aldol addition to 3-azidohexanal generated 1,3-anti products rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The results obtained in this work (Table 3) and literature precedents (Table 1) [6,10,11,21] suggest that models A2 and/ or B (Si face attack, half-chair-like transition state), which lead to the 1,3-syn diastereomer, can make a substantial impact in these addition reactions.…”
Section: Introductionsupporting
confidence: 66%
“…The results obtained in this work (Table 3) and literature precedents (Table 1) [6,10,11,21] suggest that models A2 and/ or B (Si face attack, half-chair-like transition state), which lead to the 1,3-syn diastereomer, can make a substantial impact in these addition reactions.…”
Section: Introductionsupporting
confidence: 66%
“…Most of the aldol reactions involving such aldehydes proceed in accordance with these expectations, but systematic studies on the addition of enolsilanes (42) to α-chloro, α-hydroxy, and α-amino aldehydes (43)(44)(45) revealed that their diastereoselectivity is dependent significantly on the α-heteroatom and the steric bulk of nucleophiles (Scheme 1.21) [38][39][40]. Thus, additions of acetone-derived enolsilane (42a) to aldehydes (43) and (44) possessing an electronegative α-heteroatom such as chlorine or oxygen afforded the corresponding 3,4-anti aldols (46a) and (47a) (dr 60 : 40 and 82 : 18, respectively), whereas more sterically hindered pinacolone-derived enolsilane (42c) gave under the same conditions 3,4-syn aldol (46c) or equimolar mixtures of 3,4-anti and syn diastereomers (47c).…”
Section: Mukaiyama Aldol Reactionmentioning
confidence: 79%
“…As illustrated in Scheme 1.23, most of the aldol reactions of silyl enol ethers (42) with β-hydroxy, β-chloro, and β-azido aldehydes (49) corresponding 3,5-anti aldols (50) in high diastereomeric ratios regardless of the chelating ability of the Lewis acid and the hydroxyl protecting group [42][43][44].…”
Section: 3-asymmetric Inductionmentioning
confidence: 99%
“…Huh et al 56 studied the stereoselectivity of nucleophilic addition of allylsilane to 3-azidoalkanals in the presence of chelating and non-chelating Lewis acid. Chelating Lewis acid TiCl 4 produced 1,3-syn product while non-chelating BF 3 -OEt 2 gave 1,3-anti product (Scheme 36).…”
Section: Lewis Acid Catalyzed Allylationmentioning
confidence: 99%